Ethnolinguistic research of family ritual folklore in the aspect of cultural code - Almas A. Absadyk, Miramkyl M. Kulbayeva, (Opción, 2019)
The purpose of this article is the ethnolinguistic features of the vocabulary of family ritual folklore in the Kazakh language, as well as the analysis of the methodology for studying cultural codes involved in family ritual activities via comparative qualitative research methods. As a result, the study of cultural codes is undoubtedly relevant for the analysis of the mentality of the people. In conclusion, family ritual folklore is the most complex type of reflection of reality due to the original inextricable connection with sacred acts, archaic beliefs, and realities.